Evaluation of a hormone free, natural supplement supporting oestrus induction in three different sheep genotypes - Fúró, Gabriella; Csízi, István; Bodnár, Ákos; Pajor, Ferenc; Egerszegi, István (Animal welfare, Ethology and Housing Systems (AWETH), 2022)
This study investigates the influence of the Janova hormone free natural herbal supplement on the reproductive indices of three sheep genotypes. A total of 120 sheep ewes were included in the experiment, half of them were treated according to the following genotypes: Berrichon du Cher (Berrichon, N=20), Blanc du Massif Central (BMC, N=20), and Hungarian Merino (Merino, N=20). The other half of the flock was assigned as control, also with 20-20 ewes per genotype. Overall, or among genotypes no significant relationship was detected between the control and treatment, the ewes performed similarly in the treatment and control groups. The fecundity was 75%, 115%, and 135% in the treated groups of Berrichon, BMC and Merino genotypes, and it was 65%, 95%, and 135% in the control groups, respectively. The rate of prolificacy was 115%, 153%, and 150% in the treated groups of Berrichon, BMC and Merino ewes, and it was 108%, 136%, and 141% in the control groups, respectively. The number of ewes with no lambs was 25-40% at the Berrichon and BMC genotypes (25-40%), and it was 10-15% at the Merino ewes’ (10-15%). The ratio of female and male lambs was similar at both treated and control groups, within the genotypes. Despite of the lack of statistical significance we observed promising data of fecundity and prolificacy rates, and the number of lambs born in the treated groups, thus further studies are needed to determine the efficacy of the capsule.